Exploring Islamic Economic Jalaluddin Rakhmat's Thought - Ubaidillah, Ahmad (Jurnal Ilmiah Ekonomi Islam, 2024)
This article aims to explore the ideas of Islamic economics Jalaluddin Rakhmat or who is fondly called Kang Jalal. This study uses a qualitative approach that produces descriptive data in the form of written or spoken words from people and observable behavior that aims to explain and test the truth of an economic knowledge based on Islamic values. The data sources used in this study are primary data sources and secondary data sources. The analytical method used in this research is hermeneutics. The research results show that Kang Jalal sees the importance of reviving the revolutionary spirit in eradicating poverty. That is, it is necessary to review Asy'ariyah theology and relate it to contemporary problems concerning the problem of poverty among the people. Concerning the myths of poverty, Kang Jalal categorizes the myths of poverty into three kinds. First. The myth of overgeneralization or fallacy of dramatic instances. Second. The myth of blaming the victim (blaming the victim) or argumentum ad hominem. Third. The myth of argumentum ad verecundiam. In the relationship between Sufism and poverty, Kang Jalal is more in favor of a point of view that understands Sufism as a mentality that helps overcome poverty socially rather than a mentality that encourages poverty. The results of this study also found that preaching and rational Islamic teachings about social engineering are part of the interpretation of Islamic teachings. In other words, the concept of social engineering for poverty alleviation is very relevant to the context of Islamic da'wah in Indonesia